Synthesis and Characterization of Zeolite–Chitosan Composite from North Toraja Montmorillonite Mineral: Kinetic and Isotherm Study for Cu2+ Metal Ion Adsorption - Jumianti Bunga Matande; Djabal Nur Basir; Paulina Taba; St. Fauziah; Syahruddin Kasim; Hasnah Natsir; Siti Khairunnur; Risnawati Risnawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Natural montmorillonite from North Toraja, rich in silica and alumina, was employed as a precursor for synthesize cancrinite-type zeolite (CAN) through hydrothermal treatment at 170 °C for 24 h in 5 M NaOH solution. Zeolite, a porous aluminosilicate material widely applied in wastewater treatment, especially for heavy metal ion adsorption. To enhance adsorption performance, CAN was modified with chitosan through phase inversion, resulting in the formation of a zeolite–chitosan composite. Characterization using XRD, FTIR, SEM EDS, BET, and TGA DSC. XRD analyses revealed diffraction peaks at 2θ = 13.94°, 18.84°, 21.28°, 24.16°, 27.34°, 32.42°, 34.32°, 36.76°, and 42.46°. FTIR confirmed functional groups of CANat 678, 624, and 563 cm⁻¹ and chitosan at 2879 and 1643 cm⁻¹. SEM revealed a morphological change from sharp crystals to rough surface due to chitosan coating, while EDS identified the main elements of C, O, Na, Mg, Al, and Si. BET analysis indicated a surface area of 22.12 m²/g with pore diameter of approximately 28.48 nm. TGA-DSC indicated improved thermal stability, evidenced by a shift in degradation temperature attributed to strong zeolite-chitosan interaction. Adsorption studies for Cu²⁺ ions demonstrated optimum conditions at pH of 5 with a contact time of 150 min. Kinetic data followed a pseudo-second-order model, while equilibrium was best described by the Sips isotherm, with a maximum adsorption capacity of 360.65 mg/g. These findings confirm that CAN–Chitosan composite derived from North Toraja minerals are efficient and stable adsorbents for heavy metal removal, supporting sustainable wastewater treatment and environmental remediation. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).